2002
DOI: 10.1038/sj.leu.2402552
|View full text |Cite
|
Sign up to set email alerts
|

Minimal residual disease (MRD) status prior to allogeneic stem cell transplantation is a powerful predictor for post-transplant outcome in children with ALL

Abstract: We have retrospectively investigated the relationship between the level of minimal residual disease (MRD) detected in bone marrow taken prior to conditioning therapy and outcome following stem cell transplantation for high risk childhood ALL. Forty-one patients, in whom both a molecular marker of MRD and sufficient archival material was available, were included in the study. All were in remission at BMT: eight in CR1, 32 in CR2 and five in greater than CR2. MRD was measured by PCR amplification of antigen rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
131
1
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(144 citation statements)
references
References 15 publications
9
131
1
3
Order By: Relevance
“…All of the patients selected for this study were MRD negative or low positive before the transplant, which has been shown to denote a low risk of post transplant relapse in several studies. [5][6][7][8]17 Moreover, 11 of 16 positive samples coming from patients with fusion genes were negative in simultaneous fusion transcript detection. We employed two non-self-specific RQ-PCR assays and observed a substantial percentage of false-positive amplifications in our cohort of samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the patients selected for this study were MRD negative or low positive before the transplant, which has been shown to denote a low risk of post transplant relapse in several studies. [5][6][7][8]17 Moreover, 11 of 16 positive samples coming from patients with fusion genes were negative in simultaneous fusion transcript detection. We employed two non-self-specific RQ-PCR assays and observed a substantial percentage of false-positive amplifications in our cohort of samples.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Several groups, including ours, reported the unfavorable prognostic significance of high MRD levels before transplant in children with high-risk ALL. [5][6][7][8] Studies exploring the significance of post transplant MRD were based on the detection of mixed chimerism, 9,10 flow cytometry (FC), 11 the fusion gene PCR in case of Ph þ ALL, 12 PCR using clone-specific Ig or TCR V-(D)-J sequences [13][14][15][16] and, most recently, real-time quantitative PCR (RQ-PCR) detection of clonal Ig/TCR rearrangements. 17 Consistently, all studies showed that detectable MRD at any time after SCT represents a substantial risk of post transplant relapse, both in children and in adults.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Many contemporary treatment protocols are testing the clinical utility of monitoring MRD and others have already incorporated MRD studies to aid the selection of postremission induction therapies. 12,13 MRD assays have also shown utility for patients undergoing hematopoietic stem cell transplantation, [14][15][16][17] and provide a novel parameter to assess the efficacy of emerging novel antileukemic agents. 18 Among the available methods for MRD detection in ALL, flow cytometric analysis of abnormal immunophenotypes and polymerase chain reaction (PCR) amplification of antigen-receptor genes are the most widely used.…”
Section: Introductionmentioning
confidence: 99%
“…However, outcome of patients with ALL is also poor when allogeneic SCT is performed in a non-remission status or in a status with high levels of minimal residual disease. 8 Misawa et al describe a patient with refractory RMS for which an allogeneic SCT was performed after a myeloablative regimen. The patient reached a PR.…”
mentioning
confidence: 99%